2006
DOI: 10.1590/s1807-76922006000100003
|View full text |Cite
|
Sign up to set email alerts
|

The role of food standards in international trade: assessing the brazilian beef chain

Abstract: The purpose of this paper is to identify how Brazilian beef managers have responded to a rapid expansion and intensification of standards for beef exports. This issue relates to how some Brazilian beef exporters are strategically repositioning themselves in the supply chains. The literature of this study reviews global chain governance and international standards. The method uses case studies consisting of six medium and large scale beef exporters who export fresh beef to the European Union. The main findings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 18 publications
0
3
0
1
Order By: Relevance
“…Essas questões são especificamente importantes para as empresas brasileiras, já que estas têm enfrentado crescentes pressões competitivas tanto no mercado interno (Gonçalves, Dias & Muniz, 2008) quanto no mercado internacional (Vieira, 2006). Diante desses desafios, a antecipação e o investimento em novas tecnologias podem ser fatores importantes para a eficiência e aumento de produtividade das empresas (Maça-da, Becker & Lunardi, 2005;Mendonça, Freitas & Souza, 2009 …”
Section: Introductionunclassified
“…Essas questões são especificamente importantes para as empresas brasileiras, já que estas têm enfrentado crescentes pressões competitivas tanto no mercado interno (Gonçalves, Dias & Muniz, 2008) quanto no mercado internacional (Vieira, 2006). Diante desses desafios, a antecipação e o investimento em novas tecnologias podem ser fatores importantes para a eficiência e aumento de produtividade das empresas (Maça-da, Becker & Lunardi, 2005;Mendonça, Freitas & Souza, 2009 …”
Section: Introductionunclassified
“…However, this seems to be a persistent reality if we consider the words of Contador (1996, p. 220-236), since, in accordance with him, due to the inconstant competition environment noticed in modern industrial organizations, recommendations are added to the foundations and to the classical methodologies regarding the rational planning. Vieira (2006), in her turn, has shown that the competitive environment may even be altered by factors external to the company's target activity, as in the case studied by her, the meat industry, which is very affected by aspects concerning public health. Twenty-six years have elapsed and the changing environment theme is still…”
Section: Strategies In Small Business Enterprisesmentioning
confidence: 96%
“…Other public standards are voluntary. Vieira (2006) suggested that standards are mandatory for international trade, as they are rules of measurement established by regulations or authorities and enforced by governments and enterprises. Voluntary standards are considered functionally useful tools by all industries and the US Consumer Product Safety Commission.…”
Section: Category Of Standards Referencementioning
confidence: 99%